Activation of complement by renal tissues from patients with IgA nephropathy. Issue 1 (January 1981) - Tomino, Y; Endoh, M; Nomoto, Y; Sakai, H
Abstract : In a study of complement activation by renal tissues, renal biopsy specimens were obtained from patients with IgA nephropathy and other glomerular diseases. These specimens were incubated with freshly frozen guinea-pig serum, and the activation of guinea-pig complement systems was evaluated by immunofluorescent staining with FITC-conjugated anti-guinea-pig complement antisera. It was shown that the alternative pathway of the complement was activated in situ in renal tissues from patients with IgA nephropathy. it is suggested that analysis of in situ activation of complement in such patients is useful for elucidating the mechanism of complement activation in various glomerular diseases.